LIQUIDUS TEMPERATURES OF Na3AlF6 -AlF3-CaF2-KF-LiF-Al2O3 MELTS - PENG, Jianping (Journal of Mining and Metallurgy, Section B: Metallurgy, 2014)
ABSTRACT: Temperatures for the primary crystallization of Na3AlF6-AlF3-CaF2-KF-LiF-Al2O3 system adopted in aluminum electrolysis process were determined by thermal analysis. An empirical equation was derived to describe the liquidus temperatures for the primary crystallization of this multicomponent electrolyte system: t /℃=1011 + 0.7w(AlF3) - 0.232w(AlF3)2 - 7.65w(Al2O3) + 0.523w(Al2O3)2 - 8.96w(LiF) + 0.043w(LiF)2 - 3.32w(KF) - 0.12w(KF)2 - 3.28w(CaF2) +0.037w(CaF2)2 + 0.091w(AlF3)w(LiF) + 0.074w(AlF3)w(KF) + 0.084w(AlF3)w(CaF2) - 0.27w(Al2O3)w(LiF), where w(AlF3) denotes the mass fraction of excess aluminum fluoride with respect to cryolite. While w(Al2O3) ranges from 2% to 4%, w(LiF), w(KF) and w(CaF2) from 0 to 7%, and the molar ratio of NaF/AlF3 from 2.2 to 3.